2017
DOI: 10.1186/s40942-017-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography findings in methanol toxicity

Abstract: Background Methanol toxicity poses a significant public health problem in developing countries, and in Southeast Asia, where the most common source of poisoning is via adulterated liquor in local drinks. Methanol toxicity can have devastating visual consequences and retinal specialists should be aware of the features of this toxic optic neuropathy. The authors report a case of severe systemic methanol toxicity and relatively mild optic neuropathy demonstrating unique retinal changes on optical coherence tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…The above data indicated that HU caused motor deficits associated with formaldehyde accumulation in the muscle and cerebellum. Unexpectedly, exogenous formaldehyde or methanol (a precursor of formaldehyde) has been shown to induce cerebellar ataxias in rats 15 and humans 16 . These data suggest that excessive formaldehyde in the cerebellum may be a direct trigger of acute cerebellar ataxia in the HU mouse model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The above data indicated that HU caused motor deficits associated with formaldehyde accumulation in the muscle and cerebellum. Unexpectedly, exogenous formaldehyde or methanol (a precursor of formaldehyde) has been shown to induce cerebellar ataxias in rats 15 and humans 16 . These data suggest that excessive formaldehyde in the cerebellum may be a direct trigger of acute cerebellar ataxia in the HU mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…Unsurprisingly, excessive formaldehyde had been found to markedly inactivate ATM protein and induce cell death 58 . Exogenous formaldehyde and methanol directly causes cerebellar ataxia in mice 15 and humans 16 . Formaldehyde can cause a reduction in the numbers and sizes of Purkinje cells and granular cells, and in the thickness of the granular layer in mice 59 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…También es característica en esta fase de atrofia un aumento de la excavación papilar 10 , así como un progresivo adelgazamiento de la capa de fibras peripapilares, sobre todo temporales, valorado mediante OCT; ambos hallazgos estaban presentes en nuestro paciente. Se han descrito otras alteraciones retinianas, como la aparición de microquistes en la capa nuclear interna 11 , ausentes en nuestro caso.…”
Section: Discussionunclassified
“…The resulting outcome then gets metabolized by aldehyde dehydrogenase into formic acid. Formic acid is toxic and it inhibits the mitochondrial cytochrome oxidase causing tissue hypoxia, and lactic acid [ 3 ].…”
Section: Discussionmentioning
confidence: 99%